Efficacy of fermented grain using Bacillus coagulans in reducing visceral fat among people with obesity: a randomized controlled trial - Cho, Eunbyul; Kim, Ju Young; Cho, Belong; Lee, Joong Su; Yoon, Yeo Cho; Shin, Yong Chul; Kim, Hyerim; Gil, Siye; Kim, Sohye (Frontiers in Nutrition, 2023)
Background: Obesity is a socioeconomic problem, and visceral obesity, in particular, is related to cardiovascular diseases or metabolic syndrome. Fermented grains and various microorganisms are known to help with anti-obesity effects and weight management. Studies on the relationship between Bacillus coagulans and anti-obesity effects are not well known, and studies on the application of fermented grains and microorganisms to the human body are also insufficient. Objectives: This study aimed to evaluate the efficacy of Curezyme–LAC, an ingredient mixed with six-grain types fermented by B. coagulans, in reducing fat mass in adults with obesity. Methods: In this randomized double-blinded placebo-controlled study, 100 participants (aged 40–65 years; body mass index [BMI] ≥25 to ≤33 kg/m²) were randomly allocated to two groups: 4 g/day Curezyme–LAC administered as a granulated powder or placebo (steamed grain powder mixture). Results: After 12 weeks, visceral adipose tissue decreased significantly in the Curezyme–LAC group compared with that in the placebo group (mean ± standard error, SE of -9.3 cm2 ± 5.1) vs.( 6.8 cm2 ± 3.4; p = 0.008). Compared to the placebo group, the Curezyme–LAC group also showed significant reductions in total fat mass (-0.43 ± 0.24 kg vs. 0.31 ± 0.19 kg, p = 0.011), body weight (-0.4 ±0.3 kg vs. 0.3 ±0.2 kg, p = 0.021), BMI (-0.14 ± 0.12 vs. 0.10 ± 0.07, p = 0.028), and waist circumference (-0.6 ±0.2 cm vs. -0.1 ±0.2 cm, p = 0.018) without a change in dietary intake and physical activity. Conclusions: Curezyme–LAC supplementation for 12 weeks may benefit individuals with obesity by reducing visceral fat mass.